The Relationship Between Breastfeeding Self-Efficacy and The Success of Exclusive Breastfeeding - Zulkarnaini Zulkarnaini; Hernita Hernita; Arista Ardilla (LPPM AKPER FATMAWATI, 2023)
Breast milk is the most effective way to ensure the health and safety of children. The achievement of exclusive breastfeeding in Indonesia is still relatively low. In 2018 it was only 65.16%. In the end, the obstacles experienced by the mother affect the mother's self-confidence and self-confidence in breastfeeding or it is called breastfeeding self-efficacy. This study aims to determine the relationship between breastfeeding self-efficacy and the success of exclusive breastfeeding The research design is analytic with a cross sectional study approach. The study population was mothers who have children aged 6-24 months totaling 36 people in the working area of the Muara Dua Health Center, Lhokseumawe City. The sampling technique was purposive sampling. The BSES-SF (Breastfeeding Self Efficacy Scale – Short Form) questionnaire was used in data collection. Breastfeeding self-efficacy is mostly low (52.8%), exclusive breastfeeding is mostly unsuccessful (38.9%), and there is a relationship between Breastfeeding self-efficacy and the success of exclusive breastfeeding (p value = 0.001 <0.05). There is a significant relationship between Breastfeeding Self Efficacy and the Success of Exclusive Breastfeeding.